2011
DOI: 10.1590/s1982-56762011000100003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of contact fungicide spray regimes for control of late blight (Phytophthora infestans) in southern Ethiopia using potato cultivars with different levels of host resistance

Abstract: Late blight is an important disease of potato in Ethiopia, causing up to 100% loss in susceptible cultivars. In this study, two putatively resistant cultivars of relatively recent introduction (Jalenie and Gudenie) and a widely grown susceptible cultivar (White Flower) were evaluated for late blight severity and yield under five different contact fungicide (mancozeb) regimes and in unsprayed plots. Trials were carried out at two major potato production locations in southern Ethiopia: Awassa and Kokate, located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
(20 reference statements)
0
21
0
Order By: Relevance
“…These findings showed that physico-chemical nature of the soil, geographical locations, agricultural practices and climatic conditions of the various regions had significant influence on the levels of minerals in potato. However, there is a scarcity of information regarding the level of minerals in potato cultivars grown in Ethiopia except few reports on other aspects of potato like blooming its production, paste and disease control mechanisms (Hirpa et al 2010 ; Ayalew and Beyene 2011 ; Mekonen et al 2011 ; Ayalew and Beyene 2012 ; Nigussie et al 2014 ). Ethiopia has a unique topography and climatic conditions compared to other part of the world.…”
Section: Introductionmentioning
confidence: 99%
“…These findings showed that physico-chemical nature of the soil, geographical locations, agricultural practices and climatic conditions of the various regions had significant influence on the levels of minerals in potato. However, there is a scarcity of information regarding the level of minerals in potato cultivars grown in Ethiopia except few reports on other aspects of potato like blooming its production, paste and disease control mechanisms (Hirpa et al 2010 ; Ayalew and Beyene 2011 ; Mekonen et al 2011 ; Ayalew and Beyene 2012 ; Nigussie et al 2014 ). Ethiopia has a unique topography and climatic conditions compared to other part of the world.…”
Section: Introductionmentioning
confidence: 99%
“…If not controlled, losses may reach 100% [11] and even lower infection levels may make the crop unfit for storage [12]. In the highlands of Ethiopia, late blight and bacteria wilt (Ralstonia solanacearum) are the most important potato diseases that cause an estimated yield loss of up to 70% [13].…”
Section: Methodsmentioning
confidence: 99%
“…There are many factors that reduce the yield of the crop among which the diseases like late blight (Phytophthora infestans), bacterial wilt (Ralstonia (Pseudomonas) solanacearum) and viruses play an important role [22]. In the highlands of Ethiopia, late blight and bacteria wilt (Ralstonia solanacearum) are the most important potato diseases that cause an estimated yield loss of up to 70% [13].…”
Section: Major Diseases and Insects Of Potato In Ethiopiamentioning
confidence: 99%
“…Potato late blight disease represents a serious problem for farmers in almost all major potatogrowing areas (Tsedaley 2014;Mekonen et al 2011;Kassa and Beyene 2001). On-station studies estimate yield loss 1 in Ethiopia to range from 6% to 100% depending on the level of susceptibility of the variety (Guchi 2015;Mesfin and Woldegiorgis 2007).…”
Section: Introductionmentioning
confidence: 99%